Genome-Wide Analysis of Amino Acid Transporter Gene Family Revealed That the Allele Unique to the Aus Variety Is Associated with IAmino Acid Permease 17/I - Nayak, Itishree; Sahoo, Bijayalaxmi; Pradhan, Chinmay; Balasubramaniasai, Cayalvizhi; Prabhukarthikeyan, Seenichamy Rathinam; Katara, Jawahar Lal; Meher, Jitendriya; Chung, Sang-Min; Gaafar, Abdel-Rhman Z; Hodhod, Mohamed S; Kherawat, Bhagwat Singh; Parameswaran, Chidambaranathan; et al. (Agronomy (Basel), 2023)
Amino acid transporters (AATs) play a crucial role in facilitating the movement of amino acids across cellular membranes, which is vital for the growth and development of plants. Amino acid permease (AAP), which belongs to the AAT family, has been the subject of extensive functional research in plants. Although its importance is recognized, a comprehensive grasp of this family’s dynamics in indica rice remains lacking. In this investigation, a total of 27 AAP genes were identified in the genome of indica rice. Further, the phylogenetic analysis unveiled that the 69 AAP genes from both the model species and other plant species could be classified into 16 distinct subfamilies. The analysis of chromosomal mapping revealed an uneven distribution of the 27 OsAAP genes across the 12 rice chromosomes. Notably, the OsAAP family displayed a total of 10 duplicated gene pairs, along with the identification of numerous conserved motifs. The examination of cis-elements within OsAAP genes unveiled that their promoters contain cis-elements related to phytohormones, plant growth and development, as well as stress responses. Additionally, transcriptome profiling demonstrated that a substantial portion of these genes exhibited responsiveness to various hormones, with their activation spanning multiple tissues and developmental stages in rice. The study identified miRNAs with a specific affinity for OsAAP genes. Out of the 27 OsAAP genes investigated, seventeen were discovered to be targeted by a total of forty-three miRNAs. Furthermore, the aus allele of OsAAP3 that we named OsAAP17 was validated for its effect on productive tillers and yield, and seventeen genetic variants of OsAAP17 were found to be associated with a culm number in indica rice. In addition, indica rice varieties were monomorphic, while aus genotypes displayed polymorphism for OsAAP17 gene-specific in/dels. Moreover, in Season II (rabi season), it was found that the aus allele of OsAAP17 increased the number of productive tillers and the single plant yield by 22.55% and 9.67%, respectively, in a recombinant inbred population created by crossing N22 and JR 201. Remarkably, this enhancement was more pronounced during the dry cultivation season, highlighting the influence of environmental factors in the regulation of tiller numbers mediated by OsAAP17. The discoveries presented here lay a strong foundation for further exploration into the roles of OsAAP family genes across a range of developmental processes. Therefore, the identified allelic variations in the utilization of OsAAP17 has the potential to enhance rice crop production via molecular breeding in the changing climate scenario.